2017
DOI: 10.1007/s12020-017-1460-9
|View full text |Cite
|
Sign up to set email alerts
|

Specific plasma amino acid disturbances associated with metabolic syndrome

Abstract: PurposeThe primary objective of the present study was to examine the association between branched chain and aromatic amino acid profiles (BCAA and AAA respectively) and the metabolic syndrome (MS), and to evaluate the clinical utility of these associations in the diagnostic process.MethodsTwo hundred and sixty three healthy men with MS [MS(+): n = 165] and without MS [MS(−): n = 98] were enrolled in the observational study. Anthropometrical, biochemical, and amino acid measurements were performed. The ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 61 publications
3
30
0
Order By: Relevance
“…This fact is showed in the study of the relation between circulating metabolites and abdominal obesity in twin's brothers [45] or the study revealing the predisposition to develop T2D in Chinese population [46]. Moreover, in 263 healthy men with MetS and their control counterparts, Siomkajło et al proposed a diagnostic model consisted of phenylalanine as a marker obtained from omics technologies and other classical determinations [47].…”
Section: Bcaasmentioning
confidence: 99%
“…This fact is showed in the study of the relation between circulating metabolites and abdominal obesity in twin's brothers [45] or the study revealing the predisposition to develop T2D in Chinese population [46]. Moreover, in 263 healthy men with MetS and their control counterparts, Siomkajło et al proposed a diagnostic model consisted of phenylalanine as a marker obtained from omics technologies and other classical determinations [47].…”
Section: Bcaasmentioning
confidence: 99%
“…It shows advantages in obese individuals when it is associated with physical activity, which activates fatty acid oxidation (Holecek 2018). On the other hand, the increase in BCAA plasma levels related to a reduction in amino acid catabolism may indicate type 2 diabetes mellitus (Siomkajlo et al 2017;Wang et al 2011). In this context, D r a f t BCAA supplementation could be a useful tool in the prevention of obesity or in association with a weight loss diet or a physical exercise program.…”
Section: R a F Tmentioning
confidence: 99%
“…These are essential amino acids, which participate in the regulation of body protein balance and insulin secretion, modulation of the immune system, and reduction of muscle injury post-exercise (Fan et al 2017;Holecek 2018). Elevated blood levels of BCAA are found in obesity and type 2 diabetes mellitus (Batch et al 2014;Newgard et al 2009), making them putative biomarkers of these metabolic diseases (Siomkajlo et al 2017). In contrast, a population-based study showed that a higher BCAA intake was associated with a lower prevalence of overweight and obesity (Qin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They serve as substrates for protein synthesis, glyconeogenesis, ureagenesis and precursors for syntheses of hormones and low-molecular-weight nitrogenous substances and various other catabolic processes 42 . Metabolic alterations in amino acids levels (a) essential, non-essential, conditionally essential, (b) glucogenic and ketogenic, (c) branched-chain amino acids (BCAA) and aromatic amino acids (AAA) in the serum are common in conditions of disease (e.g., cancer, diabetes) [43][44] . Amino acids serve as a key source of energy, especially during conditions in which glucose availability is limited.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%